On a new genus and species of freshwater crab from Vietnam, with comments on the nomenclatural status of Orientalia Dang, 1975 (Crustacea: Brachyura: Potamidae: Potamiscinae) - Yeo, Darren C.j.; Ng, Peter K.l. (Zootaxa, 2005)
A new potamiscine genus, Laevimon, is established for two species of semi-terrestrial freshwater crabs from Vietnam, viz., Laevimon kottelati, new species (type species) and L. tankiensis (Dang & Tran, 1992). The genus is morphologically closest to Hainanpotamon Dai, 1995, but is easily distinguished by distinct sternal and gonopodal characters. The status of Orientalia Dang, 1975, a synonym of Hainanpotamon, as a junior homonym of Orientalia Radoman, 1972 (Mollusca), is also discussed.